STRATEGI INDUSTRI PARIWISATA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN DI NUSA TENGGARA TIMUR - Apriana H.J. Fanggidae (Journal of Management Small and Medium Enterprises (SMEs), 2018)
Tourist visits will increase in line with the growing tourism industry development strategy thatincludes tourist attractions through the arrangement of space and time in the environment oftourism, human resource management strategies, implementation the quality of service, marketstrategy and strategies to build and establish cooperation with the related parties as well as thetourism policy support from the Government. In the long run, customer retention is moreprofitable than to constantly attract and cultivate new customers to replace the leaving customersKeywords : Tourism Strategy